PROTOTYPE MODUL LATIH PNEUMATIC DAN MOTOR DC BERBASIS PLC - Ria Gazali; Ismuharram Ismuharram (Institut Teknologi dan Bisnis Swadharma, 2021)
Development to realize basic technical competencies that are relevant to the conditions that will be faced in the world of work. It is necessary for teaching media or practicum media that can support and increase students' knowledge and insight regarding the technical application of these courses in the real world, especially in industry. Courses that study pneumatic systems and Programmable Logic Control (PLC) require practical media that can simulate industrial automation processes. In this paper, we will present the design of pneumatic modulation and dc motors that can be used as pneumatic system simulators and dc motors with PLC controllers. This experimental research includes the following stages: planning, manufacture, testing and finalization. This training module is designed to be portable using lightweight and easy-to-obtain materials, and is suitable for PLC learning simulations. Automated systems are represented by electro-pneumatic systems, which can apply industrial processes such as goods propulsion systems, belt conveyor systems and goods chopping systems.